2010
DOI: 10.1073/pnas.1007779107
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal–striatal pathway underlies cognitive regulation of craving

Abstract: The ability to control craving for substances that offer immediate rewards but whose long-term consumption may pose serious risks lies at the root of substance use disorders and is critical for mental and physical health. Despite its importance, the neural systems supporting this ability remain unclear. Here, we investigated this issue using functional imaging to examine neural activity in cigarette smokers, the most prevalent substance-dependent population in the United States, as they used cognitive strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
586
7
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 628 publications
(660 citation statements)
references
References 58 publications
49
586
7
9
Order By: Relevance
“…This reliance of regulation of drug motivation on attentional awareness is central to recent attempts to use attentional bias modification training (Schoenmakers et al, 2010) and attention control training (Fadardi and Cox, 2009) to reduce drugrelated attentional bias and drug use. Prior studies have demonstrated that drug-dependent individuals can regulate their craving and neural responses by the effortful cognitive regulation of drug cues (Volkow et al, 2010;Kober et al, 2010). This study adds to this literature by demonstrating that engagement of a sensory-motor-dorsal insula network is associated with decreases in the attentional bias effect for implicitly processed cocaine cues.…”
Section: Discussionsupporting
confidence: 59%
“…This reliance of regulation of drug motivation on attentional awareness is central to recent attempts to use attentional bias modification training (Schoenmakers et al, 2010) and attention control training (Fadardi and Cox, 2009) to reduce drugrelated attentional bias and drug use. Prior studies have demonstrated that drug-dependent individuals can regulate their craving and neural responses by the effortful cognitive regulation of drug cues (Volkow et al, 2010;Kober et al, 2010). This study adds to this literature by demonstrating that engagement of a sensory-motor-dorsal insula network is associated with decreases in the attentional bias effect for implicitly processed cocaine cues.…”
Section: Discussionsupporting
confidence: 59%
“…First, converging evidence suggests that enhancing psychological distance, which we construed broadly as the capacity to transcend one's egocentric viewpoint of a stimulus, facilitates self-regulation. Research in children and adults indicates, for example, that psychological distancing strategies enhance people's capacity to exert self-control when faced with tempting options in the short term (e.g., Fujita, Trope, Liberman, & Levin-Sagi, 2006;Kober et al, 2010;Mischel & Rodriguez, 1993;Sigel & McGillicuddy-De Lisi, 2003). In a similar vein, research on self-reflection indicates that cueing people to reflect on painful past experiences from a selfdistanced or "fly-on-the-wall" visual perspective helps them reflect on their experiences without ruminating (Gruber, Harvey, & Johnson, 2009;; also see Ray, Wilhelm, & Gross, 2008;Wisco & Nolen-Hoeksema, 2011).…”
Section: Harnessing Language To Promote Self-regulationmentioning
confidence: 99%
“…Following scanning (3 h after smoking), participants were shown smoking and neutral images and were asked to rate the amount of craving they experienced when viewing each image on a five-point scale. Smoking and neutral images were comprised of images from various sources including the International Smoking Image Series (Gilbert and Rabinovich, 1999) and those used in our prior work (Janes et al, 2013) and by Kober et al (2010). To control for visual characteristics, all images were converted to gray scale.…”
Section: Craving Measuresmentioning
confidence: 99%